Lessons Learned from Three Agrivoltaic Installations in New Jersey - A.J. Both; Bill Bamka; Thierry Besancon; Dunbar Birnie; Clint Burgher; Daniel Gimenez; Serpil Guran; Michael Kornitas; Pete Nitzsche; David Robinson; W. Ross Rucker; Ethan Schoolman; et al. (AgriVoltaics Conference Proceedings)
Agrivoltaics is a new technology that has the potential to positively impact commercial farming by combining agricultural practices with the generation of solar energy. While some yield reduction is to be expected, resulting from less sunlight reaching the plant canopy and ground occupied by support structures, the generated electricity provides a low-risk supplemental income to farmers. In order to combine farming with electricity generation, agrivoltaic systems use a lower ground coverage ratio compared to normal solar farms and the PV panels are often mounted higher above the ground in order to facilitate the movement of agricultural equipment and to reduce the contrast between shaded and non-shaded areas.